2015
DOI: 10.1002/ghg.1490
|View full text |Cite
|
Sign up to set email alerts
|

Jumpstarting commercial‐scale CO2capture and storage with ethylene production and enhanced oil recovery in the US Gulf

Abstract: CO 2 capture, utilization, and storage (CCUS) technology has yet to be widely deployed at a commercial scale despite multiple high-profi le demonstration projects. We suggest that developing a large-scale, visible, and fi nancially viable CCUS network could potentially overcome many barriers to deployment and jumpstart commercial-scale CCUS. To date, substantial effort has focused on technology development to reduce the costs of CO 2 capture from coal-fi red power plants. Here, we propose that near-term invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 39 publications
(57 reference statements)
0
17
0
Order By: Relevance
“…Just 1 Mt is injected for dedicated geological storage in the United States each year (the ADM project). About 4% of domestic oil production is through CO 2 -EOR (31). The size of the CO 2 -EOR industry is limited by lack of affordable carbon dioxide supply rather than a lack of potential (14,30,32,33): Oil reservoirs in the United States could store enough carbon dioxide to meet projected carbon storage requirements under a two-degree pathway until at least midcentury (7,13,29).…”
Section: Significancementioning
confidence: 99%
“…Just 1 Mt is injected for dedicated geological storage in the United States each year (the ADM project). About 4% of domestic oil production is through CO 2 -EOR (31). The size of the CO 2 -EOR industry is limited by lack of affordable carbon dioxide supply rather than a lack of potential (14,30,32,33): Oil reservoirs in the United States could store enough carbon dioxide to meet projected carbon storage requirements under a two-degree pathway until at least midcentury (7,13,29).…”
Section: Significancementioning
confidence: 99%
“…In order to identify viable CO 2 candidates for existing and planned EOR fields, ArcGIS, a geographical mapping software developed by ESRI, was used to perform spatial analysis on the basis of two key parameters: (1) minimum power generating capacity of 400 MW for sources in pathways 2 and 3 , and (2) maximum distance of 100 miles between a CO 2 pathway and an EOR oil basin. We understand that current CO 2 EOR pipelines exist from Colorado to West Texas for EOR at much greater distances (about 600 miles) . However, using similar values or even half the distance would have significant economic implications on CO 2 transport, as illustrated by the FE/NETL model .…”
Section: Methodsmentioning
confidence: 95%
“…Although the proposed strategies can play important roles in reducing GHG emissions from the transportation sector, a combined set of strategies can achieve better outcomes . Several studies have suggested the integration of carbon capture and sequestration (CCS) with CO 2 -enhanced oil recovery (EOR) as another unique approach for improving the energy outlook and reducing GHG emissions by producing crude oil with low carbon intensity. In CCS-CO 2 -EOR, carbon dioxide is sequestered and compressed from point sources, and subsequently transported and injected into mature oil reservoirs. CO 2 -EOR is a tertiary oil recovery method that has been employed by the oil industry for more than 40 years to increase pressure and recover residual oil from depleted reservoirs. , In the United States, about 60 million metric tons (MMT) of CO 2 are injected per year in EOR, which produces more than 90 million barrels of oil (MMbo) annually .…”
Section: Introductionmentioning
confidence: 99%
“…An economic evaluation of CCUS supply chains with CO2-EOR in Poland was carried out by Mathisen and Skagestad (2017) considering a sensitivity analysis for the price of oil and of carbon dioxide. In Middleton et al (2015) a CCUS supply chain was developed for the US Gulf Coast region and in nearby regions (Texas, Louisiana, Mississipi, New Mexico, Oklahoma and Kansas) reducing 50 Mton of emissions and producing 200 million bbl/yr of oil, while in Klokk et al (2010) a CO2-EOR supply chain is optimized for the Norwegian regions.…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%